Development of law for labor supervision and control in Ukraine - Terela, Halyna (ScienceRise: Juridical Science, 2023)
The study deals with the development of law for supervision and control in the field of labor in independent Ukraine to find out the condition for legal provision of supervision and control through the prism of normatively established terms, definitions, principles and taking into account the approaches, grounded in legal doctrine, regarding the social purpose of supervision and control institution in order to analyze the gaps and conflicts, ways to overcome them. To achieve the goal, we have defined the following tasks: to characterize the normative and legal acts of Ukraine directly or indirectly defining the key provisions that reveal the legal nature of supervision and control: concepts, purpose, task, scope, principles; find out the content and meaning for the provisions of ratified international and European acts regarding the features of supervision and control over compliance with labor law, the state of their implementation into national law; determine the possible options and justify the optimal one of them in terms of enshrining at the legislative level the specifics of the implementation of supervision (control) measures for compliance with labor law. There were used both general (dialectical) and general scientific (analysis and synthesis), as well as special-legal research methods (historical, hermeneutic, formal-legal, prognostic), based on the requirement of a comprehensive analysis of political and legal phenomena during the study research. Their totality made it possible determining the need to implement the norms of ILO Conventions No. 81 and No. 129 into national law and the implementation of the provisions, part six, article 2, the Law of Ukraine "On the basic principles of state supervision (control) in the sphere of economic activity", part four, article 19, the GK of Ukraine by actualizing the specifics of supervision (control) measures implementation enshrining for compliance with labor law at the legal level